2023
DOI: 10.7150/ijbs.76345
|View full text |Cite
|
Sign up to set email alerts
|

The developmental regulator HAND1 inhibits gastric carcinogenesis through enhancing ER stress apoptosis via targeting CHOP and BAK which is augmented by cisplatin

Abstract: Epigenetic disruption of tumor suppressor genes, particularly aberrant CpG methylation, plays a crucial role in gastric cancer (GC) pathogenesis. Through CpG methylome and expression profiling, a developmental transcription factor -Hand-And-Neural-crest-Derivative-expressed 1 (HAND1), was identified methylated and downregulated in GC. However, its role and underlying mechanisms in GC progression are poorly understood. Here, we show that HAND1 was frequently downregulated in GC by promoter methylation, and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our study revealed that the methylation levels of the HAND1 CpG site in CRC patients demonstrated a sensitivity of 93.33% (95% CI, 70.18–99.66%) and a specificity of 80.00% (95% CI, 62.69–90.49%), with a cut-off value greater than 1.57. It has been demonstrated that the expression of HAND1 is controlled by the promoter region, which is regulated by cytosine methylation [ 8 ]. HAND1 /2 proteins are essential in heart development, promoting cell proliferation and differentiation alongside other transcription factors like Nkx2-5 and GATA4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that the methylation levels of the HAND1 CpG site in CRC patients demonstrated a sensitivity of 93.33% (95% CI, 70.18–99.66%) and a specificity of 80.00% (95% CI, 62.69–90.49%), with a cut-off value greater than 1.57. It has been demonstrated that the expression of HAND1 is controlled by the promoter region, which is regulated by cytosine methylation [ 8 ]. HAND1 /2 proteins are essential in heart development, promoting cell proliferation and differentiation alongside other transcription factors like Nkx2-5 and GATA4.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to comprehend the multifaceted roles of these transcription factors in normal heart development and tumour formation [ 22 ]. Furthermore, studies demonstrated that the HAND1 gene was hypermethylated and downregulated in gastric cancer [ 8 ] and is believed to function as a tumour suppressor gene. These findings suggest that HAND1 gene methylation status may be a potential diagnostic biomarker for CRC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou Y et al (2021) reported that long non-coding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) significantly upregulated ERS-related proteins (XBP-1s/XBP-1U and GRP78) and apoptosis-related proteins (Bax and cleaved Caspase-3), inhibited GC cell proliferation and invasion, and promoted apoptosis. Both vivo and vitro experiments showed that the transcription factor hand and neural crest derivative expressed 1 (HAND1) upregulated expression of BIP, CHOP, ATF6, PERK, ATF4, XBP1-s and IRE1α and synergized with cisplatin in inducing GC cell lines AGS and MKN-28 apoptosis, and knockdown of CHOP attenuated this effect ( Kuang Y et al, 2023 ). Another study showed that silencing the key Calnexin gene in ERAD was able to induce SGC-7901 apoptosis accompanied by an increase in the expression levels of ERS-associated GRP94, IRE1, ATF6, and CHOP proteins ( Zhang, XH et al, 2017 ).…”
Section: Dual Effect Of Ers In Digestive System Tumorsmentioning
confidence: 99%
“…Anti-apoptotic molecules, such as Bcl-2, are frequently upregulated in cancer cells that are resistant to drug treatments [ 6 ]. The expression of BAK, a member of the Bcl-2 family, can predict chemotherapeutic responses to docetaxel in patients with GC and is an effective prognostic biomarker [ 7 ]. Recently, a growing number of genes are being recognized as biomarkers for GC, which contribute to improving the outcomes of patients with this disease.…”
Section: Introductionmentioning
confidence: 99%